THE STRATEGY OF ISLAMIC RELIGIOUS EDUCATION TEACHER IN INSTRUDING RESPONSIBILITY CHARACTER EDUCATIONAL VALUES AT MIN 10 BOYOLALI - Bibit, B; Mujiburrohman, M; Subando, Joko (Institut Islam Mamba'ul 'Ulum Surakarta, 2023)
This research aims to identify the strategies of Islamic education teachers in instilling the values of character education, particularly responsibility, in MIN 10 Boyolali. This study adopts a qualitative research method with a descriptive approach. The research subjects are Islamic education teachers at MIN 10 Boyolali, while the informants include the school principal, teachers, and students of MIN 10 Boyolali. The data collection methods used in this research are non-participant observation, interviews, and documentation. The data analysis process involves examining the research data, data reduction, and verifying the conclusions. Data validity is ensured through triangulation of data. The results show that teachers improve responsibility character education by implementing the following strategies: teaching the concept of responsibility, exemplary teachers, cultivating discipline, habituating the courage to be responsible, and creating a conducive atmosphere. With this strategy, students are expected to develop good character of responsibility and be ready to face life's challenges. Meanwhile, the character values of responsibility by teaching the concept of responsibility in a structured way, teachers can help students understand, internalize, and apply the values of responsibility in their daily lives. The teacher's example is also important in shaping student character, so the teacher must be a good role model in showing responsible attitudes and behavior.